KARAKTER AGROMORFOLOGI, DENSITAS, DAN KANDUNGAN KALSIUM OKSALAT PADA DAUN TALAS (Colocasia esculenta (L) Schott) DARI 12 AKSESI MAGELANG - Naufal Wahyu Dhiyauddin (Universitas Tidar, 2025)
The utilization of taro (Colocasia esculenta (L.) Schott) as a local food source remains suboptimal, particularly with regard to its leaves, despite their good nutritional potential. This study aims to analyze the agro-morphological characteristics, crystal density, and calcium oxalate content in 12 accessions of taro (Colocasia esculenta (L.) Schott) from Magelang City and Regency. This analysis needs to be carried out to optimize the use of taro plants as a source of nutrition and functional food that is safe and benefical for human health. The type of accession had a highly significant effect on leaf length, leaf width, and plant height. All accessions have raphide shaped calcium oxalate crystals. The highest crystal density was found in the Bogor Taro accession from Windusari and the Bogor Taro accession from Pakis, with an average of 52.04 crystals/cm², while the lowest crystal density was recorded in the Pratama 1 accession from Secang and the Black Taro accession from Bandongan, with an average of 27.15 crystals/cm². The Bogor Taro accession from Grabag had the highest crystal content at 3.15%, whereas the Black Taro accession from Bandongan had the lowest at 0.45%. Accessions (Colocasia esculenta (L.) Schott) with lower calcium oxalate content have greater potential for development as functional food ingredients that are safer for consumption.Keywords: Colocasia esculenta, agro-morphological characteristics, calcium oxalate, crystal density, food safety